Catalogue of Blattaria (Insecta) from Argentina - Crespo, Francisco Antonio; Valverde, Alejandra Del Carmen; Iglesias, Monica Sandra (Zootaxa, 2010)
An updated catalogue is given of the cockroach species recorded in Argentina. It includes a list of species, their distribution in the different provinces of the country, the institutions in which the type specimens are deposited, and an updated list of references. The results indicate 87 (plus 2 incertae sedis) species, included in 4 families, 12 subfamilies and 40 currently recognized genera. A few species are widely spread across the country, but 35% (29 + 2 incertae sedis) are only known to occur in Argentina. The biotic affinities of the biogeographic provinces were studied. The data analysis corresponds with the major areas of influence: the Neotropical and Andean regions. A parsimony analysis of endemicity (PAE) was performed. The Parana Forest, Pampa and Chaco biogeographic provinces are supported by numerous endemic species. The families Blaberidae, Blattellidae and Phyllodromiidae include 90% of the species. The cockroach fauna from Argentina is still poorly known and the number of species undoubtedly is higher. The primary homonym of Chorisoneura minuta Rocha e Silva & Aguiar, 1977 was replaced with Chorisoneura rochaesilvae nom. n.